Repeated psychological stress, chronic vicarious social defeat stress, evokes irritable bowel syndrome-like symptoms in mice - Yoshioka, Toshinori; Ohashi, Misaki; Matsumoto, Kenjiro; Omata, Tomoki; Hamano, Takumi; Yamazaki, Mayuna; Kimiki, Sayaka; Okano, Kotaro; Kobayashi, Riho; Yamada, Daisuke; Hada, Noriyasu; Kato, Shinichi; et al. (Frontiers in Neuroscience, 2022)
Increasing evidence has demonstrated that emotional states and intestinal conditions are inter-connected in so-called “brain–gut interactions.” Indeed, many psychiatric disorders are accompanied by gastrointestinal symptoms, such as the irritable bowel syndrome (IBS). However, the functional connection remains elusive, partly because there are few useful experimental animal models. Here, we focused on a highly validated animal model of stress-induced psychiatric disorders, such as depression, known as the chronic vicarious social defeat stress (cVSDS) model mice, which we prepared using exposure to repeated psychological stress, thereafter examining their intestinal conditions. In the charcoal meal test and the capsaicin-induced hyperalgesia test, cVSDS model mice showed a significantly higher intestinal transit ratio and increased visceral pain-related behaviors, respectively. These changes persisted over one month after the stress session. On the other hand, the pathological evaluations of the histological and inflammatory scores of naive and cVSDS model mice did not differ. Furthermore, keishikashakuyakuto—a kampo medicine clinically used for the treatment of IBS—normalized the intestinal motility change in cVSDS model mice. Our results indicate that cVSDS model mice present IBS-like symptoms such as chronic intestinal peristaltic changes and abdominal hyperalgesia without organic lesion. We therefore propose the cVSDS paradigm as a novel animal model of IBS with wide validity, elucidating the correlation between depressive states and intestinal abnormalities.